Bilateral nephrocalcinosis and amelogenesis imperfecta: A case report - Alok Patel; Chetana Jagtap; Chetan Bhat; Rohan Shah (Wolters Kluwer Medknow Publications, 2015)
Amelogenesis imperfecta (AI) is a group of hereditary disorders that affect the quality and/or quantity of dental enamel. This paper describes the clinicopathological features of a patient who was born of nonconsanguineous parents and who presented with oral alterations, including yellow and misshapen teeth, intrapulpal calcifications, delayed tooth eruption, and gum enlargement. Scanning electron microscopy of the teeth revealed hypoplastic enamel, and a renal ultrasound detected bilateral nephrocalcinosis, leading to a diagnosis of AI and nephrocalcinosis syndrome. Since nephrocalcinosis is often asymptomatic and can be associated with impaired renal function, dentists who see children with a generalized and thin hypoplastic AI should consider a renal ultrasound scan and referral to a Nephrologist. Children with nephrocalcinosis should also be considered for a dental check.